Municipal public spending in environmental management: efficiency and determinants - Vanderléia de Souza da Silva; Johan Hendrik Poker Junior; Marco Antonio Milani Filho; Ieda Kanashiro Makiya; Denise Rugani Topke (REVES - Revista Relações Sociais)
Brazilian public spending on environmental management is constant, being the state and the municipality of São Paulo the ones that have spent the most on this function. The preservation and care of the environment are becoming increasingly relevant in society and organizations. The public sphere manages and regulates this issue, being a key factor for public policies at all management levels. The objective of the study was to analyze the efficiency of São Paulo municipalities in managing environmental public spending, in the period from 2011 to 2015, and to identify the determinants of efficiency. The methodologies applied were Data Envelopment Analysis (DEA) to measure the efficiency and Multiple Linear Regression to identify the determinants. The DEA results indicated that the efficient municipalities each year were not those that allocated the least public resources in environmental management or those that obtained the highest environmental indicator score. The determinants of efficiency were: the overall municipal human development index; the percentages of people: with piped water and installed toilets, those with higher education above 25 years old, and the poor. Municipal efficiency was identified in municipalities that have lower impacts on the determinants. Furthermore, the results contribute to the decision-making process in the management of public spending and in the elaboration of public policies that can reduce the impacts of external factors on environmental management in the municipalities of São Paulo. And, with that, promote an increase in the environmental indicator, which consequently can bring improvements in the quality of life of citizens.